"I think it would be easier for Chinese ethnic minorities to find themselves as a minority if they go abroad": Chinese Minzu individuals' identity and the study abroad experience. (2020) - Sude,; Yuan, Mei; Chen, Ning; Dervin, Fred
Highlights: Chinese Minzu students experience complex identification during stays abroad. Cross-border experiences of Minzu students differs from that of Han students. Research on international Chinese students is enriched by studying Minzu identity. Abstract: This paper examines identity constructions of Chinese ethnic minority ( Minzu ) individuals after study abroad. International research on the 'Chinese international student' has often treated this figure as a generic and homogeneous one. Our paper calls for taking into account students' many and varied Chinese ethnic identities in the description of the study abroad experience. Based on interviews with 13 members of different ethnic minorities from Minzu University of China, who spent time abroad as part of their studies, we analyse the way they express and construct different aspects of their identity while reminiscing about their time abroad. This university is one of the most diverse universities in the world. The study is based on a poststructuralist approach to identity and interculturality abroad. A form of dialogical discourse analysis is used to examine the respondents' identity. The results show that representatives of different ethnic groups report varied experiences of 'doing' identity abroad and upon return.